Principal Strategies In Improving Students’ Learning Achievement At Smpn 5 Padang Panjang - Fitra Murni Agus R; Deguchi Agty; Prozoe Rezo (al-fikrah: Jurnal Manajemen Pendidikan, 2022)
Students’ learning achievement is the result of school achievement which depends on the principal strategies in leading and creating a design school culture or in other words designing school colour. Therefore, the study was conducted to reveal the principal’s strategies and school culture to improve students’ achievement at SMP N 5 Padang Panjang in several ways including optimally involving all school members and parents, developing profesional and teacher self-dvelopment, exploring students talents/ interests both academically and non-academicly, take an exemplary approach (touch the heart), carry out continuous supervision, make a strategy for achievements every year and giving awards and full support to students. School culture is a unity and mutual agreement made and implemented by all school members starting from principal, teachers, non-educational staff, students and even security guards. These all are manifested in attitudes, actions taken together so it becomes habitsfor all school members to create a safe, comfortable and pleasant school environment in realizing good quality education in accordance with the school’s vision and mision.